AB0676 The clinical relevance of anti-RO52 and anti-RO60 in patients in the united kingdom primary sjogren's syndrome registry (UKPSSR). (23rd January 2014) - Vila, J.; Best, K.; Mitchell, S.; Bowman, S.; Lendrem, D.; Foggo, H.; Tarn, J.; Ng, W.-F.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a multi-system autoimmune disease. Anti-Ro is the most commonly associated antibody. This can be differentiated into two subtypes, anti-Ro52 and anti-Ro60, each specific to different antigens. Clinical associations of the subtypes remain controversial in pSS. The UKPSSR is a large national cohort and biobank of over 600 clinically well characterized patients with pSS. All data and samples have been collected prospectively using a standardised proforma as previously described (1) providing a unique opportunity for analysis of the condition. Objectives: To explore whether anti-Ro52 and anti-Ro60 are associated with distinct clinical manifestations in pSS. Methods: Serum anti-Ro 52 and anti-Ro60 levels were measured using a high sensitivity Phadia assay on the first 458 UKPSSR patients as part of the interim analysis. Patients were stratified according to the presence of anti-Ro52 or anti-Ro60 and the relationship between these antibodies and clinical manifestations of pSS were examined. The EULAR Sjogren's syndrome disease activity index (ESSDAI) was used as the basis for stratification of involvement of different organs. Differences between groups were tested using Chi-squared or Fisher's exact test and Mann Whitney U tests for categorical and non-parametrical data respectively. Results: Anti-Ro52 was positive in 82% of patients and anti-Ro60 in 85%. 9 (2.0%) patients were positive for anti-Ro-52 but not anti-Ro-60, 25 (5.5%) patients were positive for anti-Ro-60 but not anti-Ro52, and 59 (12.9%) patients were negative for both antibodies. There was a significant association between anti-Ro52 and disease activity in the biological (relative risk (RR)=3.5; 95% confidence interval (CI): 2.1-5.9, p<0.0001) and articular (RR=0.9; 95%CI: 0.8-1.0, p=0.0146) domains, abnormality of Schirmer's test (RR=1.3; 95%CI: 1.2-1.5, p<0.0001) and salivary flow (RR=1.2; 95%CI: 1.0-1.4, p=0.0319). Significant association was also observed between anti-Ro60 and disease activity in the biological (RR=1.3; 95%CI: 1.2-1.4, p<0.0001) and cutaneous (RR=1.2; 95%CI: 1.1-1.2, p=0.0117) domains and Schirmer's test (RR=1.1; 95%CI: 1.0-1.3 p=0.0037). Positive anti-Ro60 was significantly associated an elevated overall ESSDAI score (p=0.031). There was no significant association between antibody status and Raynauds phenomenon, renal, haematological, central nervous system, peripheral nervous system, muscular, glandular, liver or lymph node involvement, symptom duration, fatigue severity, age or sex. Conclusions: The percentage of patients positive for both subtypes was similar in this cohort, in contrast to previous literature which showed a preponderance of anti-Ro52 in pSS. Anti-Ro-52 and anti-60 were associated with articular and cutaneous manifestations respectively. Positivity of either antibody was associated with increased disease activity in the biological domains. References: Ng WF et al, Rheumatology, 2011;50:32-9 Disclosure of Interest: None Declared